Measuring IT Governance in ERP Systems: a COBIT 2019 Evaluation of SAP Material Management Module - Putri Aulia Hariman; Melissa Indah Fianty (G-Tech: Jurnal Teknologi Terapan, 2024)
Information technology systems such as Enterprise Resource Planning (ERP) are crucial for companies to meet their business needs. However, as companies grow, challenges arise, particularly in the Material Management (MM) module within SAP. This study aims to identify issues such as data inaccuracies and material duplication during the interfacing process with SAP MM and assess IT governance capabilities using the COBIT 2019 framework. The methods used include interviews and literature review, focusing on the domains of APO12 (Managed Risk), BAI03 (Managed Solutions Identification & Build), and DSS03 (Managed Problems). The results show that APO12 reached capability level 4, while BAI03 and DSS03 are at level 3, with a target of level 4. Recommendations include enhancing proactive system design evaluation, developing systematic procedures to address data issues, and implementing permanent solutions to prevent data duplication and inaccuracies during interfacing.